Предмет: Математика,
автор: физручка
(-20)*(+1)*(-2)*(-3)*(-4)=
(-1/2)*2*(-1/3)*3*(-1/4)*4=
(-0,1)*10*(-0,2)*5*9-0,25)*4=
Ответы
Автор ответа:
0
(-20)*(+1)*(-2)*(-3)*(-4)=20*1*2*3*4=20*24=480
(-1/2)*2*(-1/3)*3*(-1/4)*4= - (1/2*2*1/3*3*1/4*4)= - 1
(-0,1)*10*(-0,2)*5*9*(-0,25)*4= - (0,1*10*0,2*5*9*0,25*4)= - (1*1*9*1)= - 9
(-1/2)*2*(-1/3)*3*(-1/4)*4= - (1/2*2*1/3*3*1/4*4)= - 1
(-0,1)*10*(-0,2)*5*9*(-0,25)*4= - (0,1*10*0,2*5*9*0,25*4)= - (1*1*9*1)= - 9
Похожие вопросы
Предмет: Английский язык,
автор: ajdynzarkyn
Предмет: Обществознание,
автор: Аноним
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: настя55настя5
Предмет: Химия,
автор: anyagorelowa20